The Pama of doe run Perú and it´s unextendable extension - Pino Herrera, Honorio (2009)
The purpose of this paper is to contribute to knowledge of environmental, economic, social and political problem generated in the mining-metallurgical complex in La Oroya as a result of the extension of thirty months of the Programa de Adecuación y Manejo Ambiental (PAMA) (suitability program and Environmental Management) , Doe Run Peru (DRP). It involves many actors. For the content of this paper has been selected main three: company, workpeople and state. I